Studying the Flow Dynamics Within Endografts in Abdominal Aortic Aneurysms - Georgakarakos, Efstratios; Xenakis, Antonios; Georgiadis, George S.; Kapoulas, Konstantinos C.; Nikolopoulos, Evagelos; Lazarides, Miltos (IntechOpen, 2012)
None